2006
DOI: 10.1002/bem.20195
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological tests and provocation of subjects with mobile phone related symptoms

Abstract: The aim of the present study was to investigate the effect of exposure to a mobile phone-like radiofrequency (RF) electromagnetic field on persons experiencing subjective symptoms when using mobile phones (MP). Twenty subjects with MP-related symptoms were recruited and matched with 20 controls without MP-related symptoms. Each subject participated in two experimental sessions, one with true exposure and one with sham exposure, in random order. In the true exposure condition, the test subjects were exposed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
1
19

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 17 publications
7
80
1
19
Order By: Relevance
“…Braune et al observed that changes in heart rate and in arterial blood pressure were independent of the EMF exposure with the use of p -statistical significance; ns -non-significant; wh -the whole group; m -men; w -women; each value represents the mean ± SD. domination of sympathetic tone in response to EMF exposure, but correlated it with emotional stress related to solving the psychophysiological tests by the participants 33) . Subjects who experienced symptoms related to MP use were recruited into the study and compared with a control group with no symptoms in association with MP use.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Braune et al observed that changes in heart rate and in arterial blood pressure were independent of the EMF exposure with the use of p -statistical significance; ns -non-significant; wh -the whole group; m -men; w -women; each value represents the mean ± SD. domination of sympathetic tone in response to EMF exposure, but correlated it with emotional stress related to solving the psychophysiological tests by the participants 33) . Subjects who experienced symptoms related to MP use were recruited into the study and compared with a control group with no symptoms in association with MP use.…”
Section: Discussionmentioning
confidence: 89%
“…In our investigation and in the rest of the discussed articles only healthy volunteers were participating. In studies conducted by Wilen et al a film was shown on a computer screen during the exposure, which could potentially have an influence on HRV 33) . The majority of subjects reported a history of MP use for 8-14 yr or 15-22 yr with a calling time more than 60 min a day or 15-60 min a day 32) .…”
Section: Discussionmentioning
confidence: 99%
“…Ancak, gruplarda yer alan deneklerin çoğunda periyotlar arasında görü-len aynı yönlü küçük değişimler, eşleştirilmiş karşılaştırmaların anlamlı fark üretmesine neden olmuştur. Literatürde yer alan çalışmaların bazılarında, CT'den kaynaklanan radyasyona bağlı olarak KHD parametrelerinde değişimler oluşmadığı (7)(8)(9)(10), bazılarında ise oluştuğu belirtilmiştir (11)(12)(13). Bu çalışmalardan sadece Andrzejak ve ark.…”
Section: Discussionunclassified
“…Literatürde, cep telefonlarının (CT) kardiyak otonomik aktivite üzerindeki etkisini, KHD analizlerini kullanarak inceleyen çalışma-lar mevcuttur (7)(8)(9)(10)(11)(12)(13). Bu çalışmalardan elde edilen sonuçlara bakıldığında, birbirleriyle çelişmekte oldukları görülmektedir.…”
Section: Introductionunclassified
“…The final sample consisted of 40 persons since one woman was excluded because of pregnancy, another due to loss of blood pressure during blood sampling and a third and a fourth could not participate for technical reasons in the statistical pair-wise analyses. Exposure was to an 890 MHz GSM signal as described previously (30,31). A specific absorption rate (SAR 1g ) of 1.0 Watt/kg to the temporal area was applied.…”
Section: Methodsmentioning
confidence: 99%